Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
1) 9(x - 3) = 9x - 27. So, 1) applies.
2) 3(3x - 9) = 9x - 27. So, 2) applies.
3) x(9x - 3) = 9[tex]x^{2}[/tex] - 3x. So, 3) dosn't apply.
4) 3(3x - 7) = 9x - 21. S0, 4) dosn't apply.
5) 3(x - 9) = 3x - 27. So, 5) also dosn't apply.
Step-by-step explanation:
1) 9(x - 3) = 9x - 27. So, 1) applies.
2) 3(3x - 9) = 9x - 27. So, 2) applies.
3) x(9x - 3) = 9[tex]x^{2}[/tex] - 3x. So, 3) dosn't apply.
4) 3(3x - 7) = 9x - 21. S0, 4) dosn't apply.
5) 3(x - 9) = 3x - 27. So, 5) also dosn't apply.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.